UTILIZATION OF LEARNING MEDIA IN ISLAMIC CULTURAL HISTORY OF MADRASAH IBTIDAIYAH (MI) - Mujib, Abdul; Ahmad Abroza; Hermawan, Rico (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Islamic Cultural History lessons are lessons that are closely related to past events, so that in the learning process many teachers teach SKI material only by telling their students. Of course, in teaching and learning activities, a student who is only told stories by his teacher eventually gets bored in learning, therefore a teacher is needed to be more creative, innovative and progressive in providing learning to students so that learning is fun and even impressive. Therefore, a teacher must or must be in this digital era, it's time to use these media in the learning process in the classroom. Learning media is very helpful for a teacher to convey the material so that it is easier and more enjoyable to be accepted by students. As for the media that can be used in the MI, there are at least two learning media that can be used, namely Visual media which is divided into still or not projected visuals and motion or projected visual media. While the use of the two instructional media in MI is audio-visual media which can be in the form of historical films or documentaries about the History of Islamic Culture.